Pathogenicity and immunogenicity of attenuated fowl adenovirus from chicken embryo liver cells in commercial broiler chickens - Mohamed Sohaimi, Norfitriah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini; Mat Isa, Nurulfiza (Nexus Academic Publishers, 2021)
Fowl adenovirus (FAdV) infection is a major viral threat to poultry industry worldwide. The virus cause Inclusion body hepatitis (IBH) outbreaks with serious economic losses and it demands an effective prevention and control measures of the disease. The objectives of this study were to determine pathogenicity and immunogenicity of live attenuated FAdV isolate (UPM1137) in commercial broiler chickens. The FAdV isolate was propagated into primary chicken embryo liver (CEL) cells for 35th passages (UPM1137CEL35) and induced several molecular changes in hexon and fiber genes at capsid region of viral protein. Sixty-four 1 day-old commercial broiler chickens were used and divided into three groups, 20 chicks in the groups A and B, and 24 chicks in the group C. The isolate with titer of 106.7TCID/ml was inoculated (0.5mL) into one-day-old chicks either via oral (Group A) or intraperitoneal (Group B) route. Control (Group C) was included and remained uninoculated. Samples of serum, liver and gizzard were collected in the chickens at day 0 post inoculation (pi) in the Control group and at days 3, 7, 14 and 21 pi in all groups. The study demonstrated neither clinical signs, nor gross and histological lesions were observed in all chickens. The isolate induced a significantly (p<0.05) high FAdV antibody titre (2348 ± 1800) at day 21pi in Group B (intraperitoneal) when compared to the Group A (oral) (190 ± 136) in the present of maternal derived antibody (MDA) (7795 ± 1414 at day-old). High antibody response at day 21pi via intraperitoneal route indicates that the viral antigen capable to circumvent MDA from neutralization due to changes in epitopes in L1 loop of hexon and knob of fiber genes. Thus, the live attenuated FAdV isolate (UPM1137CEL35) has high potential for future use against FAdV serotype 8b infection in the chickens.